Prokurator jako organ nadzoru penitencjarnego — od pełnej kontroli do utraty pozycji organu postępowania wykonawczego - Kalisz, Tomasz (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
This paper discusses the evolution of the position and role of the prosecutor in the course of shaping the institution of penitentiary supervision. Penitentiary supervision is the process of examining (controlling) the activities of the bodies established to carry out isolation measures, combined with the possibility of assistance, influence and modification of this activity. In the past, the scope of the prosecutor’s influence on the functioning of the broadly understood criminal justice system was much greater. The evolution from prosecutor supervision, through prosecutor–court supervision, to the current model of only judicial supervision, is an interesting example of a clash between two competing participants in criminal proceedings. Judicial penitentiary supervision has turned out to be more effective, and, above all, it is a guarantee of lawful and humane execution of imprisonment and pre-trial detention. The prosecutor’s supervision, especially in the period after the adoption of the 1969 Executive Penal Code, did not enjoy the same prestige as that of a judge. Prosecutors are not an independent body like judges and it was difficult to consider their decisions fully impartial. The study is a historical analysis. The time range is determined by two important normative regulations. The beginning is the decree of the Chief of State of 8 February 1919 on temporary prison regulations, where the term penitentiary supervision (performed only by a prosecutor) appears for the first time in Polish legislation. The closing date is the adoption on 6 June 1997 of the Executive Penal Code, introducing only judicial penitentiary supervision and removing it from the scopeof prosecutors’ powers.
Keywords: kara pozbawienia wolności; prokurator; niezawisłość sędziowska; nadzór penitencjarny; izolacja penitencjarna